Field-Tests versus Laboratory Methods for Determining Metal Pollutants in Soil Extracts. Issue 1 (2nd January 2020) - Zeiner, Michaela; Pirkl, Raimund; Juranović Cindrić, Iva
ABSTRACT: Soil is one of the vehicles by which metals enter plants and groundwater. Compared to organic pollutants, metals do not biodegrade and are usually not mobile. In order to estimate the potential impact on groundwater, the amount of extractable metals from soil are thus of concern. Soil matrices represent quite a complex matrix; thus, the appropriate choice of sample preparation and analytical method is of great importance and challenging to ensure reliable and fast data while keeping labor and time need as low as possible. Soil extracts using acetic acid were analyzed, on the one hand, using classical analytical methods such as titrimetry (complexometry) and spectrophotometry, and on the other hand, by instrumental methods, including inductively coupled plasma optical emission spectrometry (ICP-OES), inductively coupled plasma mass spectrometry (ICP-MS) and graphite furnace atomic absorption spectrometry (GF-AAS). The classical methods are characterized by higher limits of detection (LODs), nevertheless their application as screening method on-site is promising. Applying specific reagents, precise measurements can be obtained by photometry with LODs about 0.1 mg/L. Titrimetric methods can be used for specific single element determination and for determining the sum of certain metals at contaminated sites due to LODs around 60 mg/L.